PENGEMBANGAN KUALITAS PEMBELAJARAN AKUNTANSI PERPAJAKAN SEBAGAI UPAYA PENINGKATANKINERJA MAHASISWA - - Supriyati (Universitas Trunojoyo Madura, 2014)
This study aimed to examine the effect of the learning process to the understanding of taxation and accounting student performance. This research is a quantitative research. Data was collected through questionnaires spread directly to the students who are taking courses accounting taxation. This research completed independent sample test to each variable in terms of gender and level. In addition, it tested the effect of the learning process variables on the understanding of tax accounting and accounting understanding of the influence of taxation on student performance. This study was conducted on 62 students. Statistical tests showed that students’ perceptions of understanding of accounting and tax accounting understanding in terms of gender have the same perception, but in terms of students' perceptions of force seems to have different perception. Students' perceptions on taxation and understanding the learning process both in terms of gender and class showed that they have the same perception. Regression testing results showed that the learning process based on the learning case has no significant impact on the understanding of tax accounting, while accounting understanding has a significant influence on student performance.